Evaluation of three methods for hemoglobin measurement in a blood donor setting - Rosenblit, Jacob; Abreu, Cláudia Regina; Szterling, Leonel Nulman; Kutner, José Mauro; Hamerschlak, Nelson; Frutuoso, Paula; Paiva, Thelma Regina Silva Stracieri de; Ferreira Júnior, Orlando da Costa (São Paulo Medical Journal, 1999)
CONTEXT: The hemoglobin (Hb) level is the most-used parameter for screening blood donors for the presence of anemia, one of the most-used methods for measuring Hb levels is based on photometric detection of cyanmetahemoglobin, as an alternative to this technology, HemoCue has developed a photometric method based on the determination of azide metahemoglobin. OBJECTIVE: To evaluate the performance of three methods for hemoglobin (Hb) determination in a blood bank setting. DESIGN: Prospective study utilizing blood samples to compare methods for Hb determination. SETTING: Hemotherapy Service of the Hospital Israelita Albert Einstein, a private institution in the tertiary health care system. SAMPLE: Serial blood samples were collected from 259 individuals during the period from March to June 1996. MAIN MEASUREMENTS: Test performances and their comparisons were assessed by the analysis of coefficients of variation (CV), linear regression and mean differences. RESULTS: The CV for the three methods were: Coulter 0.68%, Cobas 0.82% and HemoCue 0.69%. There was no difference between the mean Hb determination for the three methods (p>0.05). The Coulter and Cobas methods showed the best agreement and the HemoCue method gave a lower Hb determination when compared to both the Coulter and Cobas methods. However, pairs of methods involving the HemoCue seem to have narrower limits of agreement (± 0.78 and ± 1.02) than the Coulter and Cobas combination (± 1.13). CONCLUSION: The three methods provide good agreement for hemoglobin determination.